Implementation of Good Governance Principles in Fund Management through the Supervision of the Regency Inspectorate - Ratu Milah Hamdalah; Viyulia Viyulia; Resti Oktaviani (ijd-demos, 2024)
Abstract This study aims to analyze the application of good governance principles in the management of the Village Fund in Baros Village and to evaluate the supervisory role performed by the Lebak Regency Inspectorate. Transparent and accountable Village Fund management is crucial for preventing budget misappropriation and ensuring that village development initiatives are effectively targeted. A descriptive-qualitative research method employing a case study approach was used. Primary data were collected through in-depth interviews with Inspectorate auditors, village officials, and representatives of the Village Consultative Body (BPD), while secondary data were gathered through a review of village financial reports. Data analysis was conducted interactively involving data reduction, data presentation, and conclusion drawing with validity verified through triangulation techniques. The results indicate that the application of good governance principles specifically accountability and physical transparency—in Baros Village has generally proceeded well at the formal level. However, major obstacles include weak digital transparency and administrative input errors in the Siskeudes application caused by the village officials' low level of technological literacy, as well as passive citizen participation in the oversight process. On the other hand, the Inspectorate has effectively carried out its quality assurance and consulting functions, serving as an early warning system for violations. Nevertheless, the effectiveness of this macro-level oversight is constrained by institutional limitations—such as an unfavorable auditor-to-workload ratio, limited operational budgets, and the geographical challenges of the vast Lebak Regency resulting in field inspections being limited to annual spot-check methods. Keywords: Good Governance, Village Fund, Oversight, Inspectorate, Baros Village.